Distribusi Spasial Tuberkulosis Paru Berbasis Sistem Informasi Geografis di Provinsi Jawa Barat Tahun 2023 - Windiana Nabil Qanitah; Maula Ismail Mohammad; Lina Khasanah; Bambang Karmanto (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Southeast Asia has the highest prevalence of pulmonary TB globally (45.6%), with Indonesia ranking second worldwide (9.2%). West Java Province accounts for the largest share of cases in Indonesia, representing 23% of the national total. According to the 2023 Global TB Report, the estimated number of TB cases in Indonesia reached 1,090,000, or 387 per 100,000 population. This study aims to map and describe the spatial distribution of pulmonary TB prevalence as well as risk factors, including nutritional status, smoking habits, and household contact in West Java Province using a Geographic Information System (GIS). The study design employed a quantitative analytical approach using a cross-sectional ecological method, utilizing secondary data from the 2023 Indonesian Health Survey (SKI) across 27 districts/cities in West Java Province. Spatial analysis was conducted using QGIS for mapping. The results showed that the distribution of pulmonary TB was dominated by the low category (<0.3%) in 14 areas, the moderate category (0.4–0.7%) in 11 areas, and the high category (>0.8%) in 2 areas. The risk factors of malnutrition and smoking were dominated by the moderate category, while household contact was dominated by the low category. The distribution patterns of risk factors do not always align with the distribution of pulmonary TB, indicating the presence of multidimensional influences. This mapping provides a foundation of information for more targeted pulmonary TB control interventions.